Ultrathin hematite film for photoelectrochemical water splitting enhanced with reducing graphene oxide. (8th June 2015) - Wu, Quanping; Zhao, Jun; Liu, Kan; Wang, Hongyan; Sun, Zhe; Li, Ping; Xue, Song
Abstract: Ultrathin hematite films have been prepared on FTO using a separated two-phase hydrolysis–solvothermal reaction. The film thickness can be controlled by the number of deposition cycles. The Photoanode based on hematite film with 7 deposition cycles generated a photocurrent of 0.61 mA cm −2 at +1.5 V vs. RHE. The photocurrent can be improved by coating a layer of reducing graphene oxide (RGO) through spin coating. The enhanced performance is attributed to the promoting effects of RGO which acted as hole collector and transporter in the electrodes. This research demonstrates that graphene can be used as an alternative co-catalyst to enhance photoelectrochemical water splitting activity of ultrathin hematite film. The as-prepared photoanodes were notably stable under water oxidation conditions. Highlights: Ultrathin hematite films on FTO glass were prepared using a separated two-phase hydrolysis–solvothermal reaction. The photocurrent can be improved by coating a layer of reducing graphene oxide (RGO) through spin coating. The performance enhancement are attributed to the promoting effect of RGO which acted as hole collector and transporter. A photocurrent of 0.61 mA cm −2 and IPCE of 10.4% were obtained at +1.5 V vs. RHE.